A Personal Perspective on Mario Polèse’s Research in Regional Science - Shearmur, Richard (Canadian Journal of Regional Science / Revue canadienne des sciences régionales, 2019)
In this brief paper I outline some of Mario Polèse’s work in regional economics and local development that has marked my career and which has inspired much of my own research -, first as his student, then as his colleague. Notwithstanding the importance of his work, I try to point out the other – probably more important – ways in which Mario Polèse has influenced me, and – I suspect – other students and colleagues. This influence comes more from his integrity, fearlessness and humanism than from any specific idea or paper – though these qualities also permeate his writing on regional economies and cities.